Implementing the Integrated GREEN Model for Social Natural Science Project (IPAS) to Enhance Understanding of Sustainable Biodiversity Concepts in Schools - Nayudin Hanif; Siti Fatimah; Eli Rohaeti (Postgraduate, University of Mataram, 2024)
This research implements the Garden Resources, Education, and Environment Nexus (GREEN) Model as an innovative learning strategy to enhance the sustainable understanding of biodiversity concepts through Project-Based Learning (PjBL) Science and Social Science (IPAS) subject in schools. This PjBL model aims to integrate the GREEN Model into PjBL IPAS to enhance students' understanding of biodiversity concepts at the Indonesian School in Kota Kinabalu, Sabah, Malaysia. The research employs an experimental method with a ODGE using PjBL in IPAS subjects, the sample 34 students 10th. Research instruments and data collected included a 14-item short-answer pretest-posttest, a 8-item Likert Scale questionnaires, and interview guidelines and analyzed using descriptive statistical methods. The research results indicate that the implementation of the integrated GREEN Model in PjBL IPAS can improve students' understanding of biodiversity concepts, increasing the average score from 64.85 to 83.41 with a sig (2- tailed = 0.034) < (0.05). Based on statistical analysis, the integrated GREEN Model with PiBL in subject IPAS significantly enhance students' understanding concepts of biodiversity knowledge. According to the survey and interview data processing, most students also responded positively to the learning process, finding the GREEN Model engaging and easy to understand when integrated with PjBL IPAS.